GAMBARAN PSYCHOLOGICAL WELL-BEING LANSIA DI PANTI SOSIAL TRESNA WERDHA BUDI LUHUR KOTA JAMBI: AN OVERVIEW OF ELDERLY’S PSYCHOLOGICAL WELL BEING AT TRESNA WERDHA BUDI LUHUR NURSING HOME JAMBI - Dwi Rosfah Ainayya; Jelpa Periantalo (Jurnal Psikologi Jambi, 2023)
ABSTRACT Introduction Tresna Werdha Budi Luhur Social Care Institution is a residence prepared to take care of the elders. The elders who live there are ought to adapt to the new settings in the institution. It's not uncommon to see the elderly struggle with both internal and external conflicts in the adaptation process that could affect their psychological well-being. This research aimed to describe the elders' psychological well-being in Jambi Tresna Werdha Budi Luhur Social Care Institution. Methods This research used quantitative descriptive method. The population involved in this research were the elders who live in Jambi Tresna Werdha Budi Luhur Social Care Institution. Sampling technique used was incidental sampling with total sample of 39 elders. Data were obtained by applying psychological well-being scale. Data analysis used was descriptive analysis. Results The description of the psychological well-being of the elderly at Jambi Tresna Werdha Budi Luhur Social Institution, had the highest score of 50, the lowest score of 23, and the mean score of 39.15. 18 people were classified as moderate category (46.15%), 11 people (28.21%) were classified as high category, 5 people (12.82%) were classified as low category , 4 people (10.26%) were classified as very low category, and 1 person (2.56%) was classified as very high category. Conclusions and Suggestions The level of psychological well-being of the elderly in Jambi Tresna Werdha Budi Luhur Social Institution is generally in the moderate category. Grounded on the results, the social care institution is expected to help improving the psychological well-being of the elderly who live there. Keywords: Psychological Well-Being, Elderly, Tresna Werdha Social Institution ABSTRAK Pendahuluan Panti Sosial Tresna Werdha merupakan rumah kediaman yang merawat orang lanjut usia. Lansia yang tinggal di panti tentunya harus menyesuaikan diri dengan lingkungan baru di panti. Tidak jarang pada proses tersebut mereka mengalami konflik internal maupun eksternal yang memengaruhi kondisi psychological well-being. Penelitian ini bertujuan untuk memberikan gambaran psychological well-being lansia di Panti Sosial Tresna Werdha Budi Luhur Kota Jambi. Metode Penelitian kuantitatif dengan pendekatan deskriptif. Populasi penelitian adalah lansia yang tinggal di Panti Sosial Tresna Werdha Budi Luhur Kota Jambi. Pengambilan sampel menggunakan teknik Incidental (kebetulan) dengan total subjek 39 lansia. Pengambilan data menggunakan skala alat ukur. Teknik analisis data menggunakan teknik analisis deskriptif. Hasil Gambaran psychological well-being lansia di Panti Sosial Tresna Werdha Budi Luhur Kota Jambi memiliki skor tertinggi 50, skor terendah 23, skor rata-rata sebesar 39,15 dengan klasifikasi sedang sebanyak 18 orang (46,15%), sebanyak 11 orang (28,21%) terklasifikasi tinggi, sebanyak 5 orang (12,82%) terklasifikasi rendah, sebanyak 4 orang (10,26%) klasifikasi sangat rendah, dan sebanyak 1 orang (2,56%) dengan klasifikasi sangat tinggi. Kesimpulan dan Saran Tingkat psychological well-being lansia di Panti Sosial Tresna Werdha Budi Luhur Kota Jambi umumnya berada pada kategori sedang. Dengan begitu diharapkan panti dapat membantu meningkatkan psychological well-being para lansia yang tinggal disana. Kata Kunci: Psychological Well-Being, Lansia, Panti Sosial Tresna Werdha